An investigation of a human in the loop approach to object recognition - Razeghi, Orod (2015)
For several decades researchers around the globe have been avidly investigating practical solutions to the enduring problem of understanding visual content within an image. One might think of the quest as an effort to emulate human visual system. Despite all the endeavours, the simplest of visual tasks to us humans, such as optical segmentation of objects, remain a significant challenge for machines. In a few occasions where a computer's processing power is adequate to accomplish the task, the issue of public alienation towards autonomous solutions to critical applications remains unresolved.